1969
DOI: 10.1146/annurev.ph.31.030169.003053
|View full text |Cite
|
Sign up to set email alerts
|

Biological Membranes: The Physical Basis of Ion and Nonelectrolyte Selectivity

Abstract: Basic to the function of cell membranes is the ability to select between closely similar ions and molecules, such as potassium and sodium, calcium and magnesium, alcohols and aldehydes, and esters and acids. An under standing of the principles underlying selectivity is relevant to the study of neurophysiology, active transport, passive permeation, enzyme activation, and membrane structure. The present chapter has a twofold purpose : to summarize experimental evidence concerning the distinctive and consistent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
284
5
1

Year Published

1972
1972
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 667 publications
(313 citation statements)
references
References 60 publications
23
284
5
1
Order By: Relevance
“…This same sequence (Eisenman sequence IV) has been repeatedly observed in other classes of nerve cells (e.g., squid axon: Baker et al, 1962;muscle fibers: Hagiwara et al, 1971; for sequences observed for other biological and nonbiological phenomena: cf. Diamond and Wright, 1969). There was some difficulty in obtaining exact conductance ratios to compare with the permeability ratios, since the relation between conductance and concentration appears sigmoid and ions with low conductance (Cs + and Li +) cannot be applied in sufficient concentration to evaluate the range of linearity and saturation.…”
Section: Discussionmentioning
confidence: 99%
“…This same sequence (Eisenman sequence IV) has been repeatedly observed in other classes of nerve cells (e.g., squid axon: Baker et al, 1962;muscle fibers: Hagiwara et al, 1971; for sequences observed for other biological and nonbiological phenomena: cf. Diamond and Wright, 1969). There was some difficulty in obtaining exact conductance ratios to compare with the permeability ratios, since the relation between conductance and concentration appears sigmoid and ions with low conductance (Cs + and Li +) cannot be applied in sufficient concentration to evaluate the range of linearity and saturation.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyatrazine is similar to both glyphosate and PTS in its high water solubility. The limited penetration of these compounds may be explained by the strong negative correlation between the membrane permeability of a solute and its water solubility (7).…”
Section: Methodsmentioning
confidence: 99%
“…Eisenman and Sherry sequences allow to characterize ion binding sites within the TJ pore with respect to their electrostatic interaction, which can be interpreted as different degrees of hydration shell removal (Eisenman, 1962;Diamond and Wright, 1969). Bicellular overexpression of TRIC-a resulted in decreased permeabilities to all ions tested, but only minor shifts of Eisenman and Sherry sequences, indicating that TRIC-a does not substantially alter paracellular selectivity for ions.…”
Section: Tricellulin Reduces Btj Ion Permeability Without Change In Smentioning
confidence: 99%